(Performance Evaluation and Optimization of Artificial Lift Systems in Libyan Oil Fields (Al-Farooq Journal of Sciences, 2026)
This technical study presents a comparative engineering evaluation of the most widely applied Artificial Lift Systems (Electrical Submersible Pumps ESP, Sucker Rod Pumps SRP, and Gas Lift) in mature Libyan oil fields within the Sirte Basin, based on real production field data gathered from fifteen producing wells over the dynamic 2022–2023 period. The analysis systematically employs key performance indicators (KPIs) including daily fluid production rates, failure frequency, and Mean Time Between Failures (MTBF), alongside comprehensive Nodal Analysis applications and multi-phase hydraulic simulation using industrial PROSPER and PIPESIM software tools. Final simulation results show that the Gas Lift system achieved superior operational reliability with the highest MTBF due to a robust downhole configuration completely free of moving parts. In contrast, ESP systems recorded the lowest operational reliability due to high sensitivity to free gas lock and aggressive scale deposition, while mechanical SRP systems demonstrated moderate performance heavily affected by dynamic cyclic stress and downhole asphaltene buildup. The study strongly recommends improving system selection criteria and implementing advanced engineering optimization strategies to significantly reduce operating expenditures (OPEX) and enhance sustainable economic production from mature wells.
Keywords: Artificial Lift, Nodal Analysis, Hydraulic Simulation, Production Optimization, Sirte Basin, OPEX